2021 Physics Education Research Conference Proceedings 2021
DOI: 10.1119/perc.2021.pr.yasuda
|View full text |Cite
|
Sign up to set email alerts
|

Balancing content of computerized adaptive testing for the Force Concept Inventory

Abstract: As a method to shorten the test time of the Force Concept Inventory (FCI), we previously suggested the use of Computerized Adaptive Testing (CAT). CAT is the process of administering a test on a computer, with items (i.e., questions) selected based upon the responses of the examinee to prior items. As a step to develop a CAT-based version of the FCI (FCI-CAT), we previously examined the optimal test length of the FCI-CAT such that accuracy and precision [which were measured in terms of root-mean-square error (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The FCI is used frequently in Japan (where our experiment was conducted) to measure students' understanding of mechanics. For example, Yasuda et al (2011) reported that the average score of 16 undergraduate students who attended an introductory lecture on mechanics was 70% (21 points), and the score of 5 of these students was below 60%. Kuroda et al (2017) reported the average scores of undergraduate students who attended lectures on introductory physics.…”
Section: Force Concept Inventory (Fci)mentioning
confidence: 99%
“…The FCI is used frequently in Japan (where our experiment was conducted) to measure students' understanding of mechanics. For example, Yasuda et al (2011) reported that the average score of 16 undergraduate students who attended an introductory lecture on mechanics was 70% (21 points), and the score of 5 of these students was below 60%. Kuroda et al (2017) reported the average scores of undergraduate students who attended lectures on introductory physics.…”
Section: Force Concept Inventory (Fci)mentioning
confidence: 99%